374 Impact of a Working Group on Gastrointestinal Decontamination of Pediatric Emergency in Spain. (October 2012) - Velasco, R; Acedo, Y; Del Arco, L; Salmon, N; Palacios, M
Abstract : Introduction: In a study conducted in 2001–02 including 17 pediatric emergency departments (PED) in Spain high variability was detected in management of acute pediatric intoxications and, more specifically in the gastrointestinal decontamination. Since that time, the Working Group of Intoxications (WGI) of the Spanish Pediatric Emergencies Society (SEUP) Poison designed and spread in different ways recommendations based on international guidelines based on scientific evidence about the management of these patients. The objective of this study is to analyze the impact of the measures designed by the WGI in the management of acute intoxications in PED. Patients and Methods: Comparative study cohort. We analyze the management and, specifically, gastrointestinal decontamination in three time periods in the PED included in the WGI: Group A: 2001–02, 17 PED, 2157 episodes Group B: 2008–09, 37 PED, 612 episodes Group C: 2009–11: 42 PED, 400 episodes Results: Of the 3169 episodes recorded, 1031 (32'5%)underwent for a gastrointestinal decontamination procedure (Group A: 34'1%, Group B: 27.8%, Group C: 31.5%) Of the patients who underwent gastrointestinal decontamination, technique used in each group are described in the following table . Conclusions: Recommendations developed and spread by a Working Group have approached the management of acute pediatric poisonings in Spain to international guidelines based on scientific evidence.